Launching a national sport organization loyalty program : the case of Club Hockey Canada - O'Reilly, Norm; Horning, Denyse Lafrance; Bandeh-Bahman, Ghazal (London : Human Kinetics, Inc., 2015)
This case study presents seven challenges regarding the implementation of a National Sport Organization (NSO) loyalty program. Drawing on relationship marketing and sponsorship, the case traces the evolution of the Club Hockey Canada loyalty program, managed by Hockey Canada, a large and successful NSO. The case describes the following seven challenges for managers: resource allocation, process management, branding, rules and regulations for a key element of the program (i.e., Puck Bucks), risk management, sponsorship, and cost recovery. Targeted to upper year undergraduate and graduate students in sport finance or sport marketing, the case is based on information provided by Hockey Canada and secondary research. In completing the case, students will be able to learn about the seven challenges in building a successful loyalty program.
Originally published in O'Reilly, N., Horning, D. L., & Bandeh-Bahman, G. (2015). Launching a National Sport Organization Loyalty Program: The case of Club Hockey Canada. Case Studies in Sport Management, 4(10), 54-61. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Club Hockey Canada -- Management -- Case studies; Customer loyalty programs -- Case studies; Sports -- Marketing -- Case studies